A plant growth-promoting bacteria Priestia megaterium JR48 induces plant resistance to the crucifer black rot via a salicylic acid-dependent signaling pathway - Li, Qi; Hou, Zhaoqi; Zhou, Dongqin; Jia, Mingyun; Lu, Shipeng; Yu, Jinping (Frontiers in Plant Science, 2022)
Xanthomonas campestris pv. campestris (Xcc)-induced black rot is one of the most serious diseases in cruciferous plants. Using beneficial microbes to control this disease is promising. In our preliminary work, we isolated a bacterial strain (JR48) from a vegetable field. Here, we confirmed the plant-growth-promoting (PGP) effects of JR48 in planta, and identified JR48 as a Priestia megaterium strain. We found that JR48 was able to induce plant resistance to Xcc and prime plant defense responses including hydrogen peroxide (H2O2) accumulation and callose deposition with elevated expression of defense-related genes. Further, JR48 promoted lignin biosynthesis and raised accumulation of frees salicylic acid (SA) as well as expression of pathogenesis-related (PR) genes. Finally, we confirmed that JR48-induced plant resistance and defense responses requires SA signaling pathway. Together, our results revealed that JR48 promotes plant growth and induces plant resistance to the crucifer black rot probably through reinforcing SA accumulation and response, highlighting its potential as a novel biocontrol agent in the future.